FACEBOOK AS A FORMAL INSTRUCTIONAL ENVIRONMENT IN FACILITATING L2 WRITING: IMPACTS AND CHALLENGES - Alam, Zahangir (Universitas Negeri Makassar, 2019)
In this century most of the ESL learners can be considered as digital natives due to the excessive urge and availability of technology. There are hardly any learners who aren?t exposed to any means of social network in their personal life. In use, Facebook is seen to outbalance the rest of the social networks due to its convenience and easy going approach. However, little is known about how Facebook assists learners and teachers to approach for teaching and learning ESL writing though it is found that this form of social media helps learners to socialize in their personal and academic life. Hence, this paper describes the impact and challenges of including Facebook as a formal environment in facilitating this productive skill. Results of this study indicate that using Facebook for the said purpose has had a positive impact on students? writing practices though some challenges and suggestions for future implementation were reported.